(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to identify the views of kindergarten teachers regarding the role of kindergartens in developing children’s moral values from the teachers’ perspective in the city of surman for the academic year (2025-2026). The researcher collected and analyzed the data using appropriate statistical methods and relied on the descriptive analytical approach. The study sample consisted of 30 kindergarten teachers, and after verifying the validity and reliability of the study instrument – an 18-item questionnaire distributed across three domains- the data were analyzed using relevant statistical techniques. The results revealed a strong and positive impact of kindergartens on developing children’s moral values. The findings also indicated that kindergartens play an important and influential role in fostering moral values through various educational activities. However, this role faces challenges that require serious and thoughtful solutions. Additionally, the results showed that diverse educational activities such as storytelling, theater, sports, and motivational activities have a statistically significant effect on the development of moral values.